Using a Riboswitch Sensor to Detect Co2+/Ni2+ Transport in E. coli - Wang, Xiaoying; Wei, Wei; Zhao, Jing (Frontiers in Chemistry, 2021)
Intracellular concentrations of essential mental ions must be tightly maintained to avoid metal deprivation and toxicity. However, their levels in cells are still difficult to monitor. In this report, the combination of a Co2+/Ni2+-specific riboswitch and an engineered downstream mCherry fluorescence protein allowed a highly sensitive and selective whole-cell Co2+/Ni2+ detection process. The sensors were applied to examine the resistance system of Co2+/Ni2+ in E.coli and the sensors were able to monitor the effects of genetic deletions. These results indicate that riboswitch based sensors can be employed in the study of related cellular processes.